Viviendas Art Decó en Cienfuegos - Rosa López, Eliani la (Universidad Central “Marta Abreu” de Las Villas. Facultad de Construcciones. Departamento de Arquitectura, 2018)
Dada la necesidad de propiciar el reconocimiento y la revalorización del patrimonio Art Decó en la ciudad de Cienfuegos, y completar los vacíos existentes en la historiografía de la arquitectura local y cubana, se realizó la caracterización de las edificaciones de este estilo en el Centro Histórico, expresada a partir de la definición de sus regularidades y singularidades. Se evidenció la existencia de 24 construcciones Art Decó surgidas en las décadas del treinta y cuarenta, producto de la labor de experimentados arquitectos y maestros de obras. Las soluciones formales y de enclave de esta arquitectura manifestaron rasgos identitarios portadores de gran singularidad, así como regularidades que se reflejan en la coherencia aportada a la trama y el perfil urbano.

Given the need to foster the recognition and revaluation of Art Deco heritage in the city of Santiago de Cuba, as well as filling the gaps in the historiography of the local and Cuban architecture, research was carried to characterize the buildings of this style in the Historical Center. Emphasis was given to document regularities and singularities. Criteria were proposed for the analysis of the buildings, based on, the contributions of the geographical environment, the analysis of the historiographical positions, and aspects associated with the concepts of type and typology. Results suggest the existence of more than 24 Art Deco buildings built in the 1930s and 1940s by experienced architects and master builders of Cienfuegos. Formal and locational solutions show identifying features of great singularity and also show regularities reflected in the consistency provided to the layout and the urban profile
Keywords: Arquitectura Art Decó; Centro Histórico; Cienfuegos; Patrimonio; Art Deco Architecture; Historical Centre; Heritage